Identifying the proton donor in electrocatalytic hydrogen evolution by a model hydrogenase - Riley E. Stein; Ashlee E. Wertz; Peter J. Moore; Hannah S. Shafaat (JBIC Journal of Biological Inorganic Chemistry, 2026)
Proton transfer is essential in all multi-electron transformations. Identifying the proton donor in such processes is crucial to understanding the catalytic mechanism and optimizing activity through pK a matching, which can enhance proton transfer rates. However, aqueous solutions offer multiple proton sources, which confounds clear identification of the catalytically relevant proton donor. In this work, we utilize a model hydrogenase, nickel-substituted rubredoxin (NiRd), which is capable of electrocatalytic hydrogen evolution. Prior mechanistic studies suggested a proton transfer process was involved in the rate determining step on the basis of isotopic substitution and kinetic modeling. In this study, the identity of the proton donor in this rate-determining step was investigated by employing a range of buffers with varied pK a values. The impacts of concentration and pH on catalytic currents and turnover frequencies (TOF) were investigated. These results suggest that intermolecular, buffer-dependent proton transfer is not the rate-determining step for catalysis under typical electrocatalytic conditions. Quantitative electrochemical simulations incorporating buffer information allowed extraction of intrinsic thermodynamic and kinetic parameters for catalysis. Ultimately, mechanistic distinctions between the NiRd system and other hydrogen-evolving catalysts suggest that controlling the proton donor may serve as a handle for modulating activity in an intentional manner.

Multifrequency Electrical Impedance Myography Enhanced with Machine Learning for Screening Patients with Neuromuscular Disorders - Buket Sonbas-Cobb; Seward B. Rutkove; Baoguo Wei; Sara Robicheau; W. David Arnold; Kaneshia Hives; Amy Bartlett; Peter Riley; Aleah Pagan; Stephen M. Chrzanowski; Basil T. Darras; Stephen J. Kolb (Annals of Biomedical Engineering, 2026)
Purpose We evaluated surface electrical impedance myography (EIM) enhanced with machine learning to serve as a new office-based screening tool for neuromuscular disease Methods EIM of nine muscles was successfully performed in 119 adults and 111 children (approximately half healthy and half diseased) for a total of 3158 individual muscle measurements. Multifrequency data were processed with feature engineering and classification. Nested cross-validation assessed performance, with muscle-based predictions aggregated to participant via majority voting Results Single-feature analyses showed moderate-to-good discrimination (area-under-ROC curve of 0.62–0.73). When multifrequency features were used, participant-based logistic regression and extra trees ensemble models achieved 84% accuracy with 88.1% sensitivity in adults and 93% accuracy and 94.6% sensitivity in children. Beyond classification, regression using EIM predicted muscle strength with R 2 = 0.49, outperforming single-frequency correlations Conclusion These results demonstrate that machine learning-enhanced EIM can successfully distinguish individuals with neuromuscular disease from healthy individuals. Nevertheless, further studies in larger populations of people would help advance this technology to the point that it could serve as a convenient, office-based screening tool for neuromuscular disease.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Elucidating the impact of low DO on enhanced biological phosphorus removal under aerobic and anoxic conditions at full-scale - Riley Doyle; Alexandria Gagnon; Peter A. Vanrolleghem; Charles Bott (Water Research, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Unifying the validation of ambient solar wind models - Martin A. Reiss; Karin Muglach; Richard Mullinix; Maria M. Kuznetsova; Chiu Wiegand; Manuela Temmer; Charles N. Arge; Sergio Dasso; Shing F. Fung; José Juan González-Avilés; Siegfried Gonzi; Lan Jian; et al. (Advances in Space Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Discordant population structure among rhizobium divided genomes and their legume hosts - Alex B. Riley; Michael A. Grillo; Brendan Epstein; Peter Tiffin; Katy D. Heath (Molecular Ecology, 2023)
Symbiosis often occurs between partners with distinct life history characteristics and dispersal mechanisms. Many bacterial symbionts have genomes comprising multiple replicons with distinct rates of evolution and horizontal transmission. Such differences might drive differences in population structure between hosts and symbionts and among the elements of the divided genomes of bacterial symbionts. These differences might, in turn, shape the evolution of symbiotic interactions and bacterial evolution. Here we use whole genome resequencing of a hierarchically structured sample of 191 strains of Sinorhizobium meliloti collected from 21 locations in southern Europe to characterize population structures of this bacterial symbiont, which forms a root nodule symbiosis with the host plant Medicago truncatula . S. meliloti genomes showed high local (within‐site) variation and little isolation by distance. This was particularly true for the two symbiosis elements, pSymA and pSymB, which have population structures that are similar to each other, but distinct from both the bacterial chromosome and the host plant. Given limited recombination on the chromosome, compared to the symbiosis elements, distinct population structures may result from differences in effective gene flow. Alternatively, positive or purifying selection, with little recombination, may explain distinct geographical patterns at the chromosome. Discordant population structure between hosts and symbionts indicates that geographically and genetically distinct host populations in different parts of the range might interact with genetically similar symbionts, potentially minimizing local specialization.

Taphonomic and diagenetic implications of reduction spot formation in Cretaceous red beds from the Jiaolai Basin, Eastern China - Wenzhao Fu; Peter Turner; Thomas Clements; Alan R.T. Spencer; Jifeng Yu; Yu Yang; Bangjie Guo; Zhenguo Ning; Xizhun Zhuo; Michael S. Riley; Jason Hilton (Journal of Asian Earth Sciences, 2023)

Lessons for conservation from beneath the pavement - Alexis M. Mychajliw; Elizabeth R. Ellwood; Peter S. Alagona; R. Scott Anderson; Mairin A. Balisi; Eric Biber; Justin L. Brown; Jessie George; Austin J. W. Hendy; Lila Higgins; Courtney A. Hofman; Ashley Leger; et al. (Conservation Biology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Regional trends and drivers of the global methane budget - Ann R. Stavert; Marielle Saunois; Josep G. Canadell; Benjamin Poulter; Robert B. Jackson; Pierre Regnier; Ronny Lauerwald; Peter A. Raymond; George H. Allen; Prabir K. Patra; Peter Bergamaschi; Phillipe Bousquet; et al. (Global Change Biology, 2022)
The ongoing development of the Global Carbon Project (GCP) global methane (CH 4 ) budget shows a continuation of increasing CH 4 emissions and CH 4 accumulation in the atmosphere during 2000–2017. Here, we decompose the global budget into 19 regions (18 land and 1 oceanic) and five key source sectors to spatially attribute the observed global trends. A comparison of top‐down (TD) (atmospheric and transport model‐based) and bottom‐up (BU) (inventory‐ and process model‐based) CH 4 emission estimates demonstrates robust temporal trends with CH 4 emissions increasing in 16 of the 19 regions. Five regions—China, Southeast Asia, USA, South Asia, and Brazil—account for >40% of the global total emissions (their anthropogenic and natural sources together totaling >270 Tg CH 4 yr −1 in 2008–2017). Two of these regions, China and South Asia, emit predominantly anthropogenic emissions (>75%) and together emit more than 25% of global anthropogenic emissions. China and the Middle East show the largest increases in total emission rates over the 2000 to 2017 period with regional emissions increasing by >20%. In contrast, Europe and Korea and Japan show a steady decline in CH 4 emission rates, with total emissions decreasing by ~10% between 2000 and 2017. Coal mining, waste (predominantly solid waste disposal) and livestock (especially enteric fermentation) are dominant drivers of observed emissions increases while declines appear driven by a combination of waste and fossil emission reductions. As such, together these sectors present the greatest risks of further increasing the atmospheric CH 4 burden and the greatest opportunities for greenhouse gas abatement.

Stability of tropical forest tree carbon‐water relations in a rainfall exclusion treatment through shifts in effective water uptake depth - Alexandria L. Pivovaroff; Nate G. McDowell; Tayana Barrozo Rodrigues; Tim Brodribb; Lucas A. Cernusak; Brendan Choat; Charlotte Grossiord; Yoko Ishida; Kolby J. Jardine; Susan Laurance; Riley Leff; Weibin Li; et al. (Global Change Biology, 2021)
Increasing severity and frequency of drought is predicted for large portions of the terrestrial biosphere, with major impacts already documented in wet tropical forests. Using a 4‐year rainfall exclusion experiment in the Daintree Rainforest in northeast Australia, we examined canopy tree responses to reduced precipitation and soil water availability by quantifying seasonal changes in plant hydraulic and carbon traits for 11 tree species between control and drought treatments. Even with reduced soil volumetric water content in the upper 1 m of soil in the drought treatment, we found no significant difference between treatments for predawn and midday leaf water potential, photosynthesis, stomatal conductance, foliar stable carbon isotope composition, leaf mass per area, turgor loss point, xylem vessel anatomy, or leaf and stem nonstructural carbohydrates. While empirical measurements of aboveground traits revealed homeostatic maintenance of plant water status and traits in response to reduced soil moisture, modeled belowground dynamics revealed that trees in the drought treatment shifted the depth from which water was acquired to deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change.

How do we effectively communicate air pollution to change public attitudes and behaviours? A review - Rosie Riley; Laure de Preux; Peter Capella; Cristian Mejia; Yuya Kajikawa; Audrey de Nazelle (Sustainability Science, 2021)
Solutions that engage the public are needed to tackle air pollution. Technological approaches are insufficient to bring urban air quality to recommended target levels, and miss out on opportunities to promote health more holistically through behavioural solutions, such as active travel. Behaviour change is not straightforward, however, and is more likely to be achieved when communication campaigns are based on established theory and evidence-based practices. We systematically reviewed the academic literature on air pollution communication campaigns aimed at influencing air pollution-related behaviour. Based on these findings, we developed an evidence-based framework for stimulating behaviour change through engagement. Across the 37 studies selected for analyses, we identified 28 different behaviours assessed using a variety of designs including natural and research-manipulated experiments, cross-sectional and longitudinal surveys and focus groups. While avoidance behaviour (e.g. reducing outdoor activity) followed by contributing behaviours (e.g. reducing idling) were by far the most commonly studied, supporting behaviour (e.g. civil engagement) shows promising results, with the added benefit that supporting local and national policies may eventually lead to the removal of social and physical barriers that prevent wider behavioural changes. Providing a range of actionable information will reduce disengagement due to feelings of powerlessness. Targeted localized information will appear more immediate and engaging, and positive framing will prevent cognitive dissonance whereby people rationalize their behaviour to avoid living with feelings of unease. Communicating the co-benefits of action may persuade individuals with different drivers but as an effective solution, it remains to be explored. Generally, finding ways to connect with people’s emotions, including activating social norms and identities and creating a sense of collective responsibility, provide promising yet under-explored directions. Smartphones provide unique opportunities that enable flexible and targeted engagement, but care must be taken to avoid transferring responsibility for action from national and local authorities onto individuals. Multidisciplinary teams involving artists, members of the public, community and pressure groups, policy makers, researchers, and businesses, are needed to co-create the stories and tools that can lead to effective action to tackle air pollution through behavioural solutions.

A Synthesis of the Biology and Ecology of Sculpin Species in the Laurentian Great Lakes and Implications for the Adaptive Capacity of the Benthic Ecosystem - Kelly F. Robinson; Charles R. Bronte; David B. Bunnell; Peter T. Euclide; Darryl W. Hondorp; John A. Janssen; Matthew S. Kornis; Derek H. Ogle; Will Otte; Stephen C. Riley; Mark R. Vinson; Shea L. Volkel; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Taxonomic shifts in arbuscular mycorrhizal fungal communities with shade and soil nitrogen across conventionally managed and organic coffee agroecosystems - Laura Aldrich-Wolfe; Katie L. Black; Eliza D. L. Hartmann; W. Gaya Shivega; Logan C. Schmaltz; Riley D. McGlynn; Peter G. Johnson; Rebecca J. Asheim Keller; Stefanie N. Vink (Mycorrhiza, 2020)

A conceptual framework for the identification and characterization of lacustrine spawning habitats for native lake charr Salvelinus namaycush - Stephen C. Riley; J. Ellen Marsden; Mark S. Ridgway; Christopher P. Konrad; Steven A. Farha; Thomas R. Binder; Trevor A. Middel; Peter C. Esselman; Charles C. Krueger (Environmental Biology of Fishes, 2019)

Can urban greening increase vector abundance in cities? The impact of mowing, local vegetation, and landscape composition on adult mosquito populations - Liu Yang; Katherine J. Turo; Christopher B. Riley; Edna Alfaro Inocente; Jiaxuan Tian; Nicole C. Hoekstra; Peter M. Piermarini; Mary M. Gardiner (Urban Ecosystems, 2019)

Stereoselective effects of the second-generation synthetic cathinone α-pyrrolidinopentiophenone (α-PVP): assessments of conditioned taste avoidance in rats - Katharine H. Nelson; Raul López-Arnau; Briana J. Hempel; Peter To; Hayley N. Manke; Madeline E. Crissman; Matthew M. Clasen; Kenner C. Rice; Anthony L. Riley (Psychopharmacology, 2019)

Projected change in characteristics of near surface temperature inversions for southeast Australia - Fei Ji; Jason Peter Evans; Alejandro Di Luca; Ningbo Jiang; Roman Olson; Lluis Fita; Daniel Argüeso; Lisa T.-C. Chang; Yvonne Scorgie; Matt Riley (Climate Dynamics, 2019)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Correction to: Scientific white paper on concentration-QTc modeling - Christine Garnett; Peter L. Bonate; Qianyu Dang; Georg Ferber; Dalong Huang; Jiang Liu; Devan Mehrotra; Steve Riley; Philip Sager; Christoffer Tornoe; Yaning Wang (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Scientific white paper on concentration-QTc modeling - Christine Garnett; Peter L. Bonate; Qianyu Dang; Georg Ferber; Dalong Huang; Jiang Liu; Devan Mehrotra; Steve Riley; Philip Sager; Christoffer Tornoe; Yaning Wang (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

A Wrist-Worn Piezoelectric Sensor Array for Gesture Input - Riley Booth; Peter Goldsmith (Journal of Medical and Biological Engineering, 2018)

Erratum to: Perseveration in a spatial-discrimination serial reversal learning task is differentially affected by MAO-A and MAO-B inhibition and associated with reduced anxiety and peripheral serotonin levels - Peter Zhukovsky; Johan Alsiö; Bianca Jupp; Jing Xia; Chiara Giuliano; Lucy Jenner; Jessica Griffiths; Errin Riley; Sajeed Ali; Angela C. Roberts; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2017)

Perseveration in a spatial-discrimination serial reversal learning task is differentially affected by MAO-A and MAO-B inhibition and associated with reduced anxiety and peripheral serotonin levels - Peter Zhukovsky; Johan Alsiö; Bianca Jupp; Jing Xia; Chiara Guiliano; Lucy Jenner; Jessica Griffiths; Errin Riley; Sajeed Ali; Angela C. Roberts; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2017)

Islands in the ice stream: were spawning habitats for native salmonids in the Great Lakes created by paleo‐ice streams? - Stephen C Riley; Thomas R Binder; Taaja R Tucker; John Menzies; Nick Eyles; John Janssen; Andrew M Muir; Peter C Esselman; Nigel J Wattrus; Charles C Krueger (Fish and Fisheries, 2017)
Lake trout Salvelinus namaycush , lake whitefish Coregonus clupeaformis and cisco Coregonus artedi are salmonid fishes native to the Laurentian Great Lakes that spawn on rocky substrates in the fall and early winter. After comparing the locations of spawning habitat for these species in the main basin of Lake Huron with surficial substrates and the hypothesized locations of fast‐flowing Late Wisconsinan paleo‐ice streams, we hypothesize that much of the spawning habitat for these species in Lake Huron is the result of deposition and erosion by paleo‐ice streams. This hypothesis may represent a new framework for the identification and protection of spawning habitat for these native species, some of which are currently rare or extirpated in some of the Great Lakes. We further suggest that paleo‐ice streams may have been responsible for the creation of native salmonid spawning habitat elsewhere in the Great Lakes and in other glaciated landscapes.

The Influence of Medial Substructures on Rupture in Bovine Aortas - Henry W. Haslach; Peter Riley; Aviva Molotsky (Cardiovascular Engineering and Technology, 2011)

Movements of brown smoothhounds, Mustelus henlei, in Tomales Bay, California - Brent R. Campos; Maxfield A. Fish; Gardner Jones; Rebecca W. Riley; Peter J. Allen; Peter A. Klimley; Joseph J. Cech; John T. Kelly (Environmental Biology of Fishes, 2009)

The impact of early environmental rearing condition on the discriminative stimulus effects and Fos expression induced by cocaine in adult male and female rats - Stephen J. Kohut; Peter G. Roma; Catherine M. Davis; Gerald Zernig; Alois Saria; Juan M. Dominguez; Kenner C. Rice; Anthony L. Riley (Psychopharmacology, 2009)

The effects of nicotine on ethanol-induced conditioned taste aversions in Long–Evans rats - Jennifer A. Rinker; Gregory D. Busse; Peter G. Roma; Scott A. Chen; Christina S. Barr; Anthony L. Riley (Psychopharmacology, 2008)

Synthesis and Characterisation of a Multiphosphorylated Phosphophoryn Repeat Motif; H-[Asp-(Ser(P))2]3-Asp-OH - Neil M. O’Brien-Simpson; Troy J. Attard; Ashwini Loganathan; N. Laila Huq; Keith J. Cross; Peter F. Riley; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2007)

Assessment of the aversive and rewarding effects of alcohol in Fischer and Lewis rats - Peter G. Roma; Wesley W. Flint; J. Dee Higley; Anthony L. Riley (Psychopharmacology, 2006)

Comparison of Nitrate Levels in Raw Water and Finished Water from Historical Monitoring Data on Iowa Municipal Drinking Water Supplies - Peter J. Weyer; Brian J. Smith; Zhen-Fang Feng; Jiji R. Kantamneni; David G. Riley (Environmental Monitoring and Assessment, 2006)

Rapid quantitative determination of fenitrothion on balsam fir foliage: Development of a colorimetric technique and its use in determining insecticide lifetimes on foliage - Peter J. Silk; Christopher M. Riley; Charles J. Wiesner (Archives of Environmental Contamination and Toxicology, 1988)